Expansão e evasão na universidade federal do estado de São Paulo: uma análise sobre o Reuni - Fachinetti, Tamiris Aparecida (Universidade Federal de São Carlos, 2022)
The literature shows the expansion of Brazilian Higher Education, specifically in federal universities, with the implementation of the Support Program for Federal University Restructuring and Expansion Plans - Reuni. This expansion promoted changes in economic and social aspects; in addition to some questions about the conditions of physical infrastructure and personnel that may imply the dimension of teaching quality. Thus, the theme of this research is inserted in the studies on the expansion of Brazilian public higher education, in order to analyze the evolution of Reuni in the context of dropouts in undergraduate courses at the Federal University of São Paulo, to verify the effectiveness of this federal policy in relation to the access and permanence of students in the Higher Education. By the qualitative and quantitative approach, with a theoretical basis in a critical approach to expansion, to the productive restructuring process, as well as to capital appreciation, the policy was problematized by the analysis of its implementation; calculating dropout rates at the university from 2006 to 2018; aiming to discuss the permanence in the institution. It is, therefore, a documentary research in which institutional and national documents and statistical data on dropout were selected and analyzed. Through Vincent Tinto's contributions as a theoretical foundation for dropout and permanence, university permanence policies and student maintenance actions were identified in the Reuni period, as well as continuing with the maintenance of the policies after the program has ended. Preliminary results indicate that Reuni's management assumptions were already under development in the expansion before 2007, since neoliberal expansion project to universities proposed by the government started at the institution in 2005. The investigation identified that since that date the investigated university has expanded significantly from one to five campi, but such expansion brought weaknesses in their articulation, such as intellectual segregation. In relation to dropout, quantitative surveys showed an increase in the number of dropout students. Between 2006 and 2011, the university reached the program guidelines, keeping its average rate below 10%, but as of the year 2012, rates have increased, not reaching 10%. With the conclusion of Reuni, the numbers of vacancy expansion and dropouts have not decreased, thus, it was found that the public university is discontinuous and financially unstable, which ends up damaging the entire structure that permeates the permanence of the undergraduate student. The analyzes also verified that the expansion made it possible to access the popular classes that previously did not have so many conditions to enter the undergraduate level, the offer of education in places that did not offer this modality increased, and the number of jobs, mainly for the class of professors and researchers. The results should contribute to broaden the discussion and propose debates on a topic of political and social relevance, that can contribute to a critical review of the organization, essence and the meanings of the transformations that have been taking place in Brazilian Undergraduate Education after a period of expansion.
Expansion and evasion at the federal university of the state of São Paulo: an analysis of Reuni
Keywords: Educação Superior; Expansão; Evasão; Reuni; Higher Education; Expansion; Dropout; Permanence; Reuni; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; CIENCIAS HUMANAS::CIENCIA POLITICA::ESTADO E GOVERNO::ESTRUTURA E TRANSFORMACAO DO ESTADO; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS::ANALISE INSTITUCIONAL